Organic pore heterogeneity and its impact on absorption capacity in shale reservoirs in the Wufeng and Longmaxi formations, South China - Yuying Zhang; Zhiliang He; Shuangfang Lu; Dianshi Xiao; Yifei Li; Yang Liu (Energy Geoscience)
This study aims to determine the variation and controlling factors of shale gas adsorption capacity in reservoirs in the Upper Ordovician Wufeng Formation and the Lower Silurian Longmaxi Formation (also referred to as the WF-LMX formations), South China. Based on data obtained using scanning helium ion microscopy (HIM) and nitrogen (N2) and methane (CH4) adsorption experiments, this study analyzed the organic pore heterogeneity of shales in the WF-LMX formations in well A and its effect on shale gas adsorption. Using the Frenkel-Halsey-Hill (FHH) model, data from N2 adsorption experiments were converted into fractal dimensions, which can reflect the complexity and heterogeneity of organic pores while also serving as a novel indicator for quantitatively assessing the pore structure complexity. The results indicate that shales in the WF-LMX formations in well A can be divided into two sections: (Ⅰ) the Wufeng Formation and the lower Longmaxi Formation (depths: ca. 2871.0–2898.6 m), and (Ⅱ) the upper Longmaxi Formation (depths: < 2871.0 m). Organic pores in Section Ⅰ typically exhibit complex internal structures, coarse surfaces, and interconnectivity, whereas those in Section Ⅱ are simple, smooth, and isolated. Moreover, the former possesses larger specific surface areas (SSAs) than the latter. A fractal analysis reveals that organic pores in the shale sequence can be classified into micropores (<2 nm), mesopores (2–10 nm), and macropores (>10 nm). The calculated fractal dimensions show greater heterogeneity of organic pores, especially macropores, in Section Ⅰ compared to Section Ⅱ. The results also reveal that organic macropores are the primary pores controlling the SSAs of organic pores in shale reservoirs in the WF-LMX formations. Organic pores in Section Ⅰ manifest a superior shale gas adsorption capacity compared to Section Ⅱ. The heterogeneity of organic pores might affect the adsorption capacity of shales in the formations. Generally, organic macropores in Section Ⅰ of the shale sequence exhibit more complex structures and larger SSAs, leading to a stronger absorption capacity of shale reservoirs in Section Ⅰ compared to Section Ⅱ.